Tumor mutational burden predicts the efficacy of pembrolizumab monotherapy: a pan-tumor retrospective analysis of participants with advanced solid tumors. Issue 1 (31st January 2022) - Cristescu, Razvan; Aurora-Garg, Deepti; Albright, Andrew; Xu, Lei; Liu, Xiao Qiao; Loboda, Andrey; Lang, Lixin; Jin, Fan; Rubin, Eric H; Snyder, Alexandra; Lunceford, Jared
Abstract : Background: Several studies have evaluated the relationship between tumor mutational burden (TMB) and outcomes of immune checkpoint inhibitors. In the phase II KEYNOTE-158 study of pembrolizumab monotherapy for previously treated recurrent or metastatic cancer, high TMB as assessed by the FoundationOne CDx was associated with an improved objective response rate (ORR). Methods: We retrospectively assessed the relationship between TMB and efficacy in participants with previously treated advanced solid tumors enrolled in 12 trials that evaluated pembrolizumab monotherapy, including 3 randomized trials that compared pembrolizumab with chemotherapy. TMB was assessed in formalin-fixed, paraffin-embedded pretreatment tumor samples by whole-exome sequencing. High TMB was defined as ≥175 mutations/exome. Microsatellite instability (MSI) phenotype was based on whole-exome sequencing results. Programmed death ligand 1 (PD-L1) expression was assessed by immunohistochemistry. The primary end point was ORR assessed per RECIST V.1.1 by independent central review. Other end points included progression-free survival (PFS) assessed per RECIST V.1.1 by independent central review and overall survival (OS). Results: Of the 2234 participants in the analysis, 1772 received pembrolizumab monotherapy and 462 received chemotherapy. Among the pembrolizumab-treated participants, ORR was 31.4% (95% CI 27.1 to 36.0) in the 433 participants with TMB ≥175 mutations/exome and 9.5% (95% CI 8.0 to 11.2) in the 1339 participants with TMB <175 mutations/exome. The association of TMB with ORR was observed regardless of PD-L1 expression and not driven by specific tumor types or participants with very high TMB or high MSI. In the 3 randomized controlled trials, TMB was associated with ORR (p≤0.016), PFS (p≤0.005), and OS (p≤0.029) of pembrolizumab but not of chemotherapy (p≥0.340, p≥0.643, and p≥0.174, respectively), and pembrolizumab improved efficacy versus chemotherapy in participants with TMB ≥175 mutations/exome. Conclusions: TMB ≥175 mutations/exome is associated with clinically meaningful improvement in the efficacy of pembrolizumab monotherapy and improved outcomes for pembrolizumab versus chemotherapy across a wide range of previously treated advanced solid tumor types. These data suggest TMB has broad clinical utility irrespective of tumor type, PD-L1 expression, or MSI status and support its use as a predictive biomarker for pembrolizumab monotherapy in participants with previously treated advanced solid tumors.